PEMIKIRAN IBNU HAZM TENTANG TIDAK GUGURNYA HAK HADANAH BAGI IBU YANG SUDAH MENIKAH KEMBALI DAN RELEVANSINYA TERHADAP KONTEKS INDONESIA - Aqna, Muhamad Izzul (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
The most important thing to consider following every divorce is the matter of child custody (hadanah). At this point, Ulamas differ whether the right of mothers toward custody is annulled or not should they remarry. Jumhur Ulamas argue that mother’s right is annulled in this case, but Ibnu Hazm differently argues that the mother still holds her right on child custody under condition that she could be trusted in nurturing children. From scriptural point of view (nas), the writer found the solution that the anxiety of Jumhur toward remarried mother in neglecting child’s right can be vanished should the mother and step father could be trusted both in taking care and educating the child (Ibnu Hazm). Furthermore, exposed to Indonesian legal discourse, It is argued that the book entitled al-Muhalla> written by Ibnu Hazm inevitably becomes additional source of the creation of KHI (the compilation of Islamic law). Eventually, this study confirms previous notions stating that Ibnu Hazm’s tought is relevant and applicable within Indonesian context.